1987
DOI: 10.1007/bf00314005
|View full text |Cite
|
Sign up to set email alerts
|

The behaviour of OKT3-, OKT4- and OKT8-positive cells during phases of elevated spontaneous chemiluminescence activity (CL-A) in multiple sclerosis patients

Abstract: The chemiluminescence activity (CL-A; synonym = burst activity, BA) and the percentage of OKT3-, OKT4- and OKT8-positive peripheral blood cells were serially examined in four control persons and in eight patients with multiple sclerosis. When the OKT values obtained in phases of increased CL-A (clinical remission) were compared with those of the control group, the percentage of OKT3-positive cells was reduced (P = 0.014), and that of OKT4-positive cells increased (P = 0.014); there were no significant changes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

1990
1990
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
0
3
1
Order By: Relevance
“…On the contrary, several authors have reported decreased CD8+ cell numbers in CSF [33,63,69], PB [2,26,40,46,49,64,69], and in the border area of active plaques [32,53] in MS patients. These results have been questioned by others [15,20,39,47,50,68]. Surprisingly, we found an even higher increase of CD4+/CD8+ ratio in CSF versus PB in TH patients lacking any organic disorder.…”
Section: Discussioncontrasting
confidence: 83%
See 1 more Smart Citation
“…On the contrary, several authors have reported decreased CD8+ cell numbers in CSF [33,63,69], PB [2,26,40,46,49,64,69], and in the border area of active plaques [32,53] in MS patients. These results have been questioned by others [15,20,39,47,50,68]. Surprisingly, we found an even higher increase of CD4+/CD8+ ratio in CSF versus PB in TH patients lacking any organic disorder.…”
Section: Discussioncontrasting
confidence: 83%
“…This result is in agreement with reports of Rose et al [48], Zabriskie et al [68], Matsui et al [33], Capra et al [7], Salonen et al [49], Uitdehaag et al [63], and Thompson et al [57], although the latter found some elevation ofthe CD4+/CD8+ ratio along with increased disability of MS patients. Increased CD4+/CD8+ ratios have also been reported for PB [2,15,28,40,46,64,69] and for PB-derived T-cell lines [11] in MS patients. Our patient material is too small to allow any conclusions on T-cell subsets in relation to disease variables.…”
Section: Discussionmentioning
confidence: 86%
“…These studies were grouped by their system of research. The most commonly studied system of research was blood cells (9) [40], [41], [42], [43], [44], [45], [46], [47], [48] followed by whole body (8) [49], [50], [51], [52], [53], [54], [55], [56], blood plasma (4) [39], [57], [58], [59], tissues (2) [60], [61], urine (2) [62], [63], saliva (1) [64], and other cells (1) [65].…”
Section: Resultsmentioning
confidence: 99%
“…When researchers established links among oxidation, free radical production, and an increase in BE, this led to further investigation of using BE as a means to measure an individual’s health ( E. P. Wijk & Wijk, 2005 ; R. Van Wijk, 2001 ). Recent studies have shown an association of increased BE in multiple sclerosis patients ( Hammann et al, 1987 ), ankylosing spondylitis ( K. J. Ho et al, 2000 ), and in chronic lung disease ( Koval’chuk et al, 1998 ). This increase in BE during stress, illness, and disease ( Grasso et al, 1992 ; Keshavarzian et al, 1992 ; E. P. Van Wijk et al, 2010 ) corresponds to a number of studies that show that BE decreases in healthful behavior such as meditation ( E. P. Van Wijk et al, 2006 ; E. P. Van Wijk et al 2008a ; E. P. Van Wijk et al, 2008b ).…”
Section: Introductionmentioning
confidence: 99%